Facing adversity together by looking beyond ability: An approach to resilience among at-risk children and youth. - Ruiz-Román, Cristóbal; Juárez-Pérez-Cea, Jesús; Molina-Cuesta, Lorena (Taylor & Francis, 2019)
Resilience has become a very popular concept in recent years. More and more social intervention models and practices are increasingly being based on this concept. However, far from being a closed and static notion, it is very dynamic and constantly evolving. This paper presents an analysis of how the concept of resilience and the studies about it have developed over time. The literature on resilience shows that the concept has shifted from an approach that identified it as a personal quality towards an approach that understands it as a set of actions activated from different spheres. The latest advances in studies on resilience raise the prospect of some elements that, going beyond the individual’s ability, should be taken into account from a social practice perspective. This study will therefore highlight and analyse the potential of these elements in the co-creation of actions and synergies for resilience.
https://openpolicyfinder.jisc.ac.uk/id/publication/5250
Keywords: Desarrollo comunitario; Resiliencia (Psicología); Community development; Resilience; Empowerment; Educational relationships